I invented the modern age [compact disc, unabridged] : the rise of Henry Ford - Snow, Richard, 1947- (Tantor Media, Inc., 2013)
From acclaimed popular historian Richard Snow comes a fresh and entertaining account of Henry Ford and his invention of the Model T, the ugly, cranky, invincible machine that defined twentieth-century America.